2012
DOI: 10.1017/s0959270912000457
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal changes of foraging habitats and prey species in the Japanese Crested Ibis Nipponia nippon reintroduced on Sado Island, Japan

Abstract: SummarySeasonal foraging habitats, prey species and foraging frequency of Japanese Crested Ibis Nipponia nippon in farmland were studied one year after its reintroduction on Sado Island, Japan. Paddies were the main foraging habitat in spring, early summer, autumn and winter. In late summer, ibises often used levees around paddies, grasslands, uncropped paddies and abandoned paddies. Small invertebrates were important prey components in terms of frequency (70–90%) throughout the year. Ibises took Misgurnus loa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 14 publications
0
10
0
Order By: Relevance
“…However, there are several activities intended to restore abandoned farmlands to original natural ecosystems in areas with high potential and needs for rewilding. On Sado island, abandoned paddies function as foraging habitats of the reintroduced Crested Ibis, Nipponia nippon [ 89 ], and in the Lake Inbanuma watershed, abandoned paddies on small valley bottoms have potential for multipurpose usages such as flood control, water purification, and wetland biodiversity [ 90 ]. In Hokkaido, the abandoned farmlands could be used to harbor organisms of wetland ecosystems [ 84 87 ] and provide wetland green infrastructure [ 91 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, there are several activities intended to restore abandoned farmlands to original natural ecosystems in areas with high potential and needs for rewilding. On Sado island, abandoned paddies function as foraging habitats of the reintroduced Crested Ibis, Nipponia nippon [ 89 ], and in the Lake Inbanuma watershed, abandoned paddies on small valley bottoms have potential for multipurpose usages such as flood control, water purification, and wetland biodiversity [ 90 ]. In Hokkaido, the abandoned farmlands could be used to harbor organisms of wetland ecosystems [ 84 87 ] and provide wetland green infrastructure [ 91 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, these studies mainly described rice fields as seasonally limited surrogate wet habitats as a source of food for wetland birds. For example, Endo and Nagata (2013) reported that the reintroduced Japanese crested ibis (Nipponia nippon) on Sado Island, Japan adapted to rice fields as a core food source as well as obtaining food from surrounding habitats during the annual single-cropping rice cultivation calendar. Masero et al (2011) reported that, in the west coastal area of the Iberian Peninsula, as a substitute for natural large-scale wetlands, rice fields have become a major habitat for long-distance migratory shorebirds, particularly during winter pooling.…”
Section: Asian Openbill Habitat Adaptationmentioning
confidence: 99%
“…In satoyama , traditional agricultural landscapes of Japan, various types of animals [e.g. Japanese marten ( Tatara and Doi 1994 ), moles ( Yokohata 2005 ), birds ( Minamiya et al 2007 , Nagata 2010 , Endo and Nagata 2013 ), frogs ( Hirai and Matsui 2000 , Hirai and Matsui 2001 ) and carabid beetles ( Okuzaki et al 2010 )] feed on earthworms. Thus, earthworms contribute to the sustainability of food webs in satoyama .…”
Section: Introductionmentioning
confidence: 99%
“…Since re-introduction, the wild population of crested ibis has been steadily increasing; the recent population estimate is 368 wild individuals in 2018 ( Bansho 2019 ). According to a recent study, wild crested ibis feed on earthworms on the levees of rice paddy margins, especially in the summer ( Endo and Nagata 2013 ). However, the species composition and density of earthworms within levee grasslands on the island have not been examined.…”
Section: Introductionmentioning
confidence: 99%